Post-marketing safety of immunomodulatory drugs in multiple myeloma: A pharmacovigilance investigation based on the FDA adverse event reporting system - Jiang, Tingting; Su, Hui; Li, Yanping; Wu, Yuanlin; Ming, Yue; Li, Chen; Fu, Ruoqiu; Feng, Lu; Li, Ziwei; Li, Li; Ni, Rui; Liu, Yao (Frontiers in Pharmacology, 2022)
Objective: In recent years, the emergence of immunomodulatory drugs (IMiDs) has significantly improved clinical outcomes in patients with multiple myeloma (MM); however, serious adverse events (AEs) have hindered their safe clinical application. This study aimed to characterize the safety profiles and differences in IMiDs through a disproportionality analysis using the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS), a post-marketing surveillance database. Methods: This study filtered reports of thalidomide, lenalidomide, and pomalidomide as primary suspect drugs in FAERS files from January 2013 to December 2021. AEs in the reports were retrieved according to the preferred terms (PTs) of the Medical Dictionary for Regulatory Activities. Furthermore, we detected safety signals using the reporting odds ratio (ROR), proportional reporting ratio (PRR), and Bayesian belief propagation neural network (BCPNN). When all three algorithms showed an association between the target drug and the AE, a positive signal was generated. Results: We extracted 9,968 thalidomide, 231,926 lenalidomide, and 55,066 pomalidomide AE reports. AEs were more common in male patients and in those >44 years old. Important safety signals were detected based on the system organ classes (SOC), including thalidomide (cardiac disorders: ROR, 2.87; PRR, 2.79; IC 1.22), lenalidomide (gastrointestinal disorders: ROR, 2.38; PRR, 2.27; IC 0.75), and pomalidomide (respiratory, thoracic, and mediastinal disorders: ROR, 2.14; PRR, 2.09; IC 0.85). Within the PT level, we identified novel risk signals: the thalidomide-induced second primary malignancy (SPM) signal was significant; lenalidomide reduced the success rate of hematopoietic stem cell collection; and three IMiDs may cause human chorionic gonadotropin increase, but this needs to be proven by clinical data. Pneumonia, sepsis, and renal failure are common risk factors for death due to IMiDs. Compared with thalidomide and lenalidomide, pomalidomide has a lower risk of venous thromboembolism (VTE) and is beneficial to patients with renal insufficiency. Conclusion: Mining data from FAERS resulted in novel AE signals, including adenocarcinoma of colon, harvest failure of blood stem cells, and increased levels of human chorionic gonadotropin. Further investigation is required to verify the significance of these signals. Moreover, IMiDs showed differences in safety reports, which should be emphasized by clinicians.